Diversification of Transit Risks of Oil Supplies Bypassing Ukraine as the Basis of Energy Security in Europe - Chernysheva, Anna M.; Gusakov, Nikolay P.; Trofimova, Alexandra A.; Bulatenko, Mariya A. (International Journal of Energy Economics and Policy, 2019)
The article assesses and analyzes the dependence of the economic security of the European Union on the transit risks of oil, the difficulties of its transportation and diversification of its supplies. The oil transportation system of Ukraine is currently a source of high risks for the EU countries because the political and economic instability of the country does not provide confidence in obtaining the planned supply contracts. To diversify oil transit risks, the following ways were identified: Baltic Pipeline System-1, Baltic Pipeline System-2, Caspian Pipeline Consortium-1 (CPC-1), Caspian Pipeline Consortium-2 (CPC-2). At that, the implementation of the latter will reduce transit risks to a minimum level by diversifying oil supplies from Russia to the EU countries. The use of the Druzhba Oil Pipeline and the Odessa-Brody Oil Pipeline increases the transit risks for the EU countries since they pass through the territory of Ukraine, which is characterized by political and economic instability. In the methodological part of the article, an assessment of oil consumption in the countries of Central and Eastern Europe was carried out, which had shown a slight decrease in Russian oil consumption just in some countries, while sustainable consumption in general. Oil supplies to Ukraine are significantly reduced that further increases the transit risk. Keywords: Baltic Pipeline System, Caspian Pipeline Consortium, energy security, oil pipeline, power industry JEL Classifications: Q43, Q48, F13 DOI: https://doi.org/10.32479/ijeep.8428